Smartphone use in telepractice for voice disorders. A review from Mhealth concept - Rodríguez Marconi, Daniel; Morales, Camilo; Araya, Polette; Ferrada, Richard; Ibarra, Manuel; Catrifol, Maria Teresa (Revista de Investigación en Logopedia, 2022)
The use of smartphones and the concept of Mobile Health (mHealth) is recent in vocology and its possible benefits in the treatment and vocal training in telepractice context. A narrative review was carried out with the objective of describing the benefits of mHealth through the smartphone in the context of speech therapy telepractice in vocal disorders. A search was conducted for articles in Pubmed, ScienceDirect and Google Scholar, in studies associated with the use of the smartphone in vocology, considering normal human voices, pathological and synthetic voices, related to intervention, evaluation, assessment, monitoring, prevention, intervention, supervision, education, consultation and training. A total of 42 studies were obtained, of which 15 were selected according to the inclusion criteria. The studies analyzed are related to voice recording for acoustic analysis with a smartphone, teletherapy with a smartphone, and peripheral devices for vocal analysis and monitoring. The potential of mobile devices to increase accessibility, reduce costs and favor therapeutic follow-up with objective measures in various contexts of vocal health is highlighted.